Impact of Dysmenorrhea on Academic Performance Among Haramaya University Undergraduate Regular Students, Eastern Ethiopia - Mesele, Tiruye Tilahun; Ayalew, Hiwotie Getaneh; Syoum, Asmra Tesfahun; Antehneh, Tazeb Alemu (Frontiers in Reproductive Health, 2022)
ABSTRACT Background: Dysmenorrhea is the most common gynecological problem among students and affects students’ academic performance. Even though, studies carried out in Ethiopia, primarily focused on the prevalence aspects rather than the impacts of dysmenorrhea on academic performance and associated factors. Therefore, this study focused on the prevalence of the impact of dysmenorrhea on academic performance and its associated factors among Haramaya university undergraduate female students in eastern Ethiopia. Methods: A cross-sectional study design was conducted from February to March 2020. A multistage random sampling technique was applied and a total of 356 students were included in the study. To select students, simple random sampling was used and the sample size was proportionally allocated with respect total number of each selected department. A Semi-structured and pre-tested self-administered questionnaire was used. The descriptive result was presented in proportion whereas the analytic part was presented with an adjusted odds ratio. Result: The prevalence of impact of dysmenorrhea on academic performance was 266((74.7%):95%CI[70.0%,79.5%]).Premenstrual syndrome(AOR=4.86:95%CI[2.13,11.06]) ,early menarche(AOR=4.89:95%CI[2.03,11.77]),Moderate/severe dysmenorrhea pain intensity(AOR=8.53:95%CI[4.45,16.39]) and students monthly pocket money <150ETB (AOR=3.91:95%CI [1.48, 10.29]) were significantly associated with the occurrence of impact of dysmenorrhea on academic performance. The most common impacts were difficult to study followed by loss of concentration in the class. Conclusion and Recommendation: There was a high prevalence of impact of dysmenorrhea on academic performance among Haramaya university undergraduate female students. Awareness should be created to Haramaya university authorities and teachers about the academic performance impact of premenstrual syndrome and dysmenorrhea pain intensity to provide a psychological, academic, and managing mechanism for the affected students. Haramaya University is better to establish medical care for the affected students. Keywords: Dysmenorrhea, Ethiopia, academic performance, absenteeism, impact.